Speech Acts in Early Childhood: A Case Study of Pragmatic Development in Two-Year-Olds - Sudding, Muhammad Fahri Jaya; Sembiring, Surya Anantatama; Musdalifah, Musdalifah; Azhari, Ahmad (ELT Worldwide: Journal of English Language Teaching, 2025)
This study investigates the emergence of pragmatic competence in early childhood through the analysis of speech acts performed by two children aged 2 years and 3 months (Child 1) and 2 years and 5 months (Child 2). Through the lens of Austin’s and Searle’s speech act theory, the qualitative study focuses on spontaneous utterances that are collected during natural interactions, such as play and daily routines. The findings reveal that even at a very young age, children are capable of performing various speech acts, including asserting, requesting, refusing, and expressing ownership which indicate their growing ability to use language intentionally and effectively. The analysis highlights the presence of locutionary, illocutionary, and perlocutionary acts in the children’s speech, promoting the view that pragmatic competence begins to develop well before formal schooling. These results contribute to a deeper understanding of early language development and provide insight into the cognitive and communicative abilities of young children.